2015
DOI: 10.1016/j.pupt.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The 24-h lung-function profile of once-daily tiotropium and olodaterol fixed-dose combination in chronic obstructive pulmonary disease

Abstract: Overall, this study demonstrated improvements in lung function over 24 h with an FDC of tiotropium + olodaterol over tiotropium or olodaterol alone, with no observed difference in tolerability. ClinicalTrials.gov number: NCT01559116.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 20 publications
5
90
1
9
Order By: Relevance
“…GFF MDI treatment amounted to a decrease of approximately half a liter in FRC and RV vs placebo MDI (13% and 22%, respectively), which is consistent with the reduction in FRI airway resistance observed and implies a reduction in air trapping and hyperinflation. These results are similar to those reported for two placebo-controlled LAMA/LABA studies of aclidinium/formoterol (400/12 μg; 4 weeks) and tiotropium/olodaterol (2.5/5 μg and 5/5 μg; 6 weeks), which reported change from baseline improvements vs placebo in an FRC of 366–535 mL and in RV in the region of 465–660 mL 25,26…”
Section: Discussionsupporting
confidence: 86%
“…GFF MDI treatment amounted to a decrease of approximately half a liter in FRC and RV vs placebo MDI (13% and 22%, respectively), which is consistent with the reduction in FRI airway resistance observed and implies a reduction in air trapping and hyperinflation. These results are similar to those reported for two placebo-controlled LAMA/LABA studies of aclidinium/formoterol (400/12 μg; 4 weeks) and tiotropium/olodaterol (2.5/5 μg and 5/5 μg; 6 weeks), which reported change from baseline improvements vs placebo in an FRC of 366–535 mL and in RV in the region of 465–660 mL 25,26…”
Section: Discussionsupporting
confidence: 86%
“…Recently, the use of LAMAs, LABAs, and their combination has been shown to play a highly effective central role in the maintenance therapy of COPD [23,24]. The present study also indicates the potential role of SABA assist use for stable COPD.…”
Section: Resultssupporting
confidence: 63%
“…We observed a higher-than-expected response with tiotropium, with a response versus placebo MDI for the primary endpoint of 224 mL, compared with 107 and 199 mL observed in Phase III studies at Week 12 and Week 6, respectively [17, 20]. Whilst a peak FEV 1 of approximately 360 mL was observed for open-label tiotropium on Days 7 and 14 of this trial, previous studies have reported lower values for this endpoint, ranging from 240 to 280 mL [22, 23].…”
Section: Discussionmentioning
confidence: 98%